386 Achieving Ldl Cholesterol Target In A Real-World Secondary Prevention Cohort: When Two Is Better Than One. (17th December 2020) - Casula, Matteo; Taietti, Ivan; Zeqaj, Iris; Fortuni, Federico; Cornara, Stefano; Somaschini, Alberto; Leonardi, Sergio; Ferlini, Marco; Camporotondo, Rita; Totaro, Rossana; Gnecchi, Massimiliano
Abstract: Aims: Lipid management plays a key role in secondary prevention after acute coronary syndrome. Current European Society of Cardiology guidelines recommend a dual goal: to achieve LDL cholesterol (LDL-C) <55 mg/dL, and to reduce it ≥ 50% form baseline. Currently, data on the reduction of cardiovascular events in patients achieving both goals in a real-world population are missing. Accordingly, the objective of this study was to determine the prognosis in post myocardial infarction (PMI) patients and determine the risk of new events according to the achievement of the optimal goals indicated by the guidelines in terms of LDL-C reduction. Methods and results: We conducted a retrospective analysis of a monocentric observational registry prospectively enrolling patients admitted to our hospital for ST segment elevation myocardial infarction (STEMI) and followed-up in our dedicated PMI ambulatory. The analysis considered the patients enrolled between 2013 and 2017. Demographical and clinical data were extracted from a dedicated digital database, and the clinical events occurred during follow-up were obtained by telephone interviews or clinical records. We considered a combined endpoint of major adverse cardiovascular events (MACE) of all-cause death, non-fatal MI, non-fatal stroke and unplanned revascularization. LDL-C was collected at baseline and at 1, 6 and 12 months after the event. The lower value collected at follow-up was used to define the achievement of the target goals. We conducted a Kaplan-Meier analysis and log-rank test comparing patients who achieved LDL-C < 55 mg/dL and ≤50% from baseline (group A) vs those with only LDL-C < 55 mg/dL (group B). Continue variable are presented as median (interquartile range). A total of 814 patients (23% female) were included in our analysis. Median age was 63 (55–72) years, 57% had hypertension, 19% diabetes, 36% were smoker and 17% obese. Baseline LDL-C was 124 (97–146) mg/dL, the median LDL-C at follow-up was 63 (52–78) mg/dL, significantly reduced from baseline ( P  < 0.0001). Between 6 and 12 months 83.3% of patients were treated with statin therapy alone (73% high intensity), 15.3% with the addition of ezetimibe, and 0.5% with ezetimibe alone. LDL-C < 55 mg/dl was achieved in 244 patients (30%), while 175 patients (21%) obtained also LDL-C ≤ 50% from baseline. Median follow-up was 52 (34–66) months. The net incidence of MACE was 12% in group A vs 27.5% in group B (HR 0.35; 95% CI 0.17–0.70; P log-rank = 0.0032; Number Needed to Treat = 6; see Figure). Conclusion: Our data from a real-world cohort of PMI patients emphasize the importance of achieving both the guideline-recommended secondary prevention goals of LDL-C < 55 mg/dl and ≤50% from baseline in order to reduce MACE.